Keragaman Morfometrik dan Genetik Gen COI Belut Sawah (Monopterus albus) Asal Empat Populasi di Jawa Barat - Lella Herdiana; Muhammad Mukhlis Kamal; Nurlisa Alias Butet; Ridwan Affandi (Jurnal Ilmu Pertanian Indonesia, 2017)
Swamp eel (Monopterus albus) is an economically important freshwater fish which has the potential to sustainable development. This species is considered as one of the taxonomically problematic spesies due to its complex characters and similar morphology to Monopterus cuchia and Monopterus javanensis that often lead to taxonomic dilemmas. Taxonomic certainty is an essential basis information in sustainable fisheries management, studies on morphometric characters, and genetic variability is a method which commonly used for species or stock identification. This study was aimed to validate the taxonomy certainty and evaluate the kinship of swamp eel from four populations (Indramayu, Subang, Tasikmalaya, and Garut distrik) in West Java. Morphometric analysis was conducted by measurement of 19 characters, whereas genetic analysis was conducted using PCR-Sequencing method of COI gene. The results from stepwise discriminant analysis showed that 7 morphometric characters ratio were powerful to classified the populations and the first two discriminant functions accounted 84.2% of the total variability. Genetic diversity indicated by alignment 14 sekuen of COI gene showed there were 11 haplotypes from 109 variable sites. Results of cluster and phylogenetic tree analysis indicated that swamp eel from four research populations were grouped into two major clusters. The first cluster consists of Indramayu and Subang population, the second cluster consists of Tasikmalaya and Garut population. This cluster is an evidence that swamp eel from West Java possesed morphometric and genetic diversity among populations and lead to assumption that at least there were two cryptic species from M. albus in West Java.